2020
DOI: 10.1021/acs.jpcb.0c07535
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Excellent π–π Interactions in Poly(thiophene)s To Reach a High Third-Order Nonlinear Optical Response

Abstract: Poly­(thiophene)­s have an inherently large third-order nonlinear optical (TONO) response, but applications are not straightforward due to unoptimized materials. Therefore, several structure–property relationships (molar mass, branching, regioregularity) are investigated to unravel which structural modifications give the highest TONO response. Poly­(3-hexylthiophene) with different molar masses, poly­[3-(2-ethylhexyl)­thiophene] with different molar masses, and random copolymers with different degrees of regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…According to the Spano model, P2 possesses stronger π-π interactions. Since previous research demonstrated that excellent π-π interactions give rise to a large TONO response, 46 the larger TONO response of P2 compared to P1 can be explained by the stronger π-π interactions present. However, since the strength of the π-π interactions between P2 and P3 is the same, they cannot be responsible for the difference in TONO response, meaning that the topology is responsible as it is the only varying parameter between P2 and P3.…”
Section: Scheme 1: Representation Of the Synthetic Pathway To Obtain P1-p3mentioning
confidence: 94%
See 2 more Smart Citations
“…According to the Spano model, P2 possesses stronger π-π interactions. Since previous research demonstrated that excellent π-π interactions give rise to a large TONO response, 46 the larger TONO response of P2 compared to P1 can be explained by the stronger π-π interactions present. However, since the strength of the π-π interactions between P2 and P3 is the same, they cannot be responsible for the difference in TONO response, meaning that the topology is responsible as it is the only varying parameter between P2 and P3.…”
Section: Scheme 1: Representation Of the Synthetic Pathway To Obtain P1-p3mentioning
confidence: 94%
“…Note that the obtained <γ> are in the same range with <γ> obtained from previous research on poly(thiophene)s. This confirms that poly(thiophene)s lead to a high TONO response. 46 For the linear polymers, P1 and P2, P2 shows a higher <γ> as a result of enhanced π-π interactions. While, when the trigonal nonlinear polymer is compared to its linear counterpart P2, the trigonal nonlinear topology does not give a higher <γ>.…”
Section: Scheme 1: Representation Of the Synthetic Pathway To Obtain P1-p3mentioning
confidence: 95%
See 1 more Smart Citation
“…Anodic chlorination is a typical ePF reaction that has been well investigated in our previous studies. [30][31][32][33][34][35] P3EHT is known to exhibit a semicrystalline character, [36][37][38][39] which suggests that the structure of P3EHT can be controlled by changing the film-preparation process. Therefore, P3EHT is a suitable precursor polymer for investigating the effects of the film structure on the efficacy of ePF.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the well-known applications such as organic photovoltaics 1−3 and polymer organic light-emitting diodes, 4−7 CPs have shown great promise in applications using Faraday rotation 8−10 and second-and third-order nonlinear optics. 11 Nevertheless, the potential of CPs has yet to reach its limit. This is proven by the recent evolution in which the optoelectronic properties and excellent processability of CPs are found to be a perfect match with the high electron mobility and unique photonic properties of inorganic nanoparticles (NPs).…”
Section: ■ Introductionmentioning
confidence: 99%